Migration Planning Framework for Legacy Systems’ Cloud Migration - Riihimäki, Santtu (My University, 2023)
Cloud computing is being adopted at a fast phase by organizations all over the world. By utilizing cloud computing, significant benefits compared to traditional on-premises solutions can be achieved. Most of the new systems and applications are built to be cloud native applications but many large organizations still depend on legacy systems that have been built tens of years ago. Migrating these legacy applications or systems to the cloud have become major objective for the organizations. Legacy applications and systems have their own concerns and risks regarding cloud migration and require profound evaluation before the migration process can even be started. In this thesis, literature review was done to identify the possible migration strategies as well as common concerns and risks regarding legacy system’s or application’s cloud migration. Literature review was utilized to build a migration planning framework for legacy system’s or application’s cloud migration. The migration planning framework was validated with a case study. In the case study, a legacy application’s tentative cloud migration was planned by utilizing the created migration planning framework.
Keywords: cloud migration, cloud computing, legacy system, migration planning framework, migration strategy